Treatment of fantasy and realist sections in Alasdair Gray's "Lanark" and Salmon Rushdie's "Midnight's Children" - Polak, Iva (Array, 2004)
The goal of this paper is to juxtapose and compare two fictional works, Gray’ s Lanark and Rushdie’ s Midnight’ s Children, as works that exploit the same or similar textual strategies – oscillation between realist and fantasy sections – but are construed from a different place of utterance. As it will be shown, this different place of production enables the reading of Lanark as a postmodernist work questioning and playing with the fixed notion of time and space, and the established literary genres, whereas Midnight’ s Children challenges the accepted Western historicity by using the technique of magic realism in the attempt to restore the history of the former British colony.